Personal/impersonal and subject/null subject phenomena in the multi-structural languages - Muryasov, Rakhim Z.; Zheltukhina, Marina R.; Sergeeva, Olga V. (XLinguae, 2024)
The study examines the functional potential of impersonal pronouns in different languages. The aim of this study is to analyze personal/impersonal and subject/null subject phenomena in multi-structural languages. The novelty of the study is to establish the role of the pronoun in personal and impersonal aspects. To achieve the aim of the study, the following methods are used: lexico-grammatical analysis, structural analysis, contrast analysis, and interpretative analysis of artistic and lexicographic texts. The comparative research was based on Russian, English, German, and French lexicographic resources and examples from artistic discourse in Russian, English, German, and French with their translations. As a result of the study, it was revealed that the impersonal pronoun is a homonym for the personal pronoun of the 3rd person unit. In grammatical studies, the impersonal pronoun stands out as an independent category. A unit known in grammar as the 3rd person pronoun (in German es, in English it, in French il, ce) has a broader functional potential than other pronouns. Namely, it can act in the text not only as a substitute for another word but can also indicate syntactic structures of different complexity: from a word to a complex of propositions. The prospect is to study the discursive nature of impersonality in various types of discourse in different linguocultures.